Artificial Intelligence Research and Development : Proceedings of the 12th International Conference of the Catalan Association for Artificial Intelligence - Sandri, Sandra (Sandra Aparecida); Sànchez-Marrè, M. (Miquel); Cortés, U. (Ulises) (Frontiers in artificial intelligence and applications, 2009)
"This book is a collection of 45 accepted papers originally submitted for the 12th International Conference of the Catalan Association for Artificial Intelligence (ACIA). It also includes a brief summary of two papers from invited speakers. The Catalan Association for Artificial Intelligence was founded in 1994 with the aim of fostering cooperation among researchers from the Catalan-speaking AI research community. Collaboration between ACIA members and the wider international AI community has also been well-established now for many years. The papers in these proceedings reflect this collaboration and include contributions not only from the Catalan-speaking regions of Spain, but also from France and Italy, and from as far afield as Mexico and Australia. Of all the computer sciences, AI is the one most intertwined with all sorts of disciplines dealt with in the human experience, often employing lessons learnt in one discipline to implement a task in another. The papers in this volume reflect the rich diversity inside AI, covering areas such as logics, natural language, machine learning, computer vision, robotics and multi-agent systems."--Jacket.